-4x+71=43

Simple and best practice solution for -4x+71=43 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4x+71=43 equation:


Simplifying
-4x + 71 = 43

Reorder the terms:
71 + -4x = 43

Solving
71 + -4x = 43

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-71' to each side of the equation.
71 + -71 + -4x = 43 + -71

Combine like terms: 71 + -71 = 0
0 + -4x = 43 + -71
-4x = 43 + -71

Combine like terms: 43 + -71 = -28
-4x = -28

Divide each side by '-4'.
x = 7

Simplifying
x = 7

See similar equations:

| 2t^2+10t-8=0 | | 5x^3+2y-10= | | 30+-6x=18 | | 25y=.394*25 | | 2x+3+5=130 | | 1-999999999+3h= | | 8-99+u= | | 35+3y=-6 | | Ssquared+20s+100=0 | | 8+3=524 | | 2.41-3.67= | | 11x-38=180 | | X^2+17.3x-81=0 | | 1/12*100 | | 8(-1+x)+3=2(m-5.5) | | 5x+5x=10x^2 | | 4x^2-1-cotx=0 | | 60x^2-50=0 | | 10x+12y=200 | | 14x^2-82x+60=0 | | 12x12/4x4 | | x^2-x-300=0 | | 15x^2-81x+30=0 | | 5(3+x)+(2+x)=0.3(x+1) | | x+7x+21=11 | | f(x)=2/4-9x^2 | | 2x^2+24X=-64 | | 10/x-4=x/50 | | 2x+24x=-64 | | 0=-16t^2+10t+1255 | | 36x+49=26 | | 10k-3k-5h= |

Equations solver categories